Histogenesis of the cysts in the autosomal dominant polycystic kidney disease: An immunohistochemical study - Therezo, Altino Luiz Silva; Bacchi, Carlos Eduardo; Franco, Marcello (Wolters Kluwer, 1998)
The histogenesis of the cysts in the autosomal dominant polycystic kidney disease was investigated in 33 patients by immunohistochemistry. The antibodies and lectins used to identify the different segments of the nephrons were as follows: vimentin-parietal epithelium of the glomerular capsule; lotus tetragonolubus agglutinin and anti-CD15-proximal tubule; anti- Tamm-Horsfall protein (THP)-distal tubule (DT); anti-epithelial membrane antigen, anti-cytokeratin 19, Ulex europaeus agglutinin, Arachis hypogaea agglutinin (PNA), Dolichos biflorus agglutinin and Glycine maximum agglutinin (SBA)-DT and collecting duct. In a pilot study, we analyzed three normal autopsy kidneys (control kidneys) and noninvolved areas of two kidneys with autosomal dominant polycystic kidney disease (internal control) and observed in all cases that glomerular capsule stained with vimentin, proximal tubule with lotus tetragonolubus agglutinin and CD15, DT with THP, DT and collecting duct with epithelial membrane antigen, anti-cytokeratin 19, Ulex europaeus- I, PNA, and Dolichos biflorus agglutinin. SBA was nonreactive. The 49 kidneys with autosomal dominant polycystic kidney disease gave the following immunohistochemical profile: (a) noninvolved areas: antivimentin-glomerular capsule = 82%; lotus tetragonolubus agglutinin-proximal tubule = 96%; anti- CD15-proximal tubule = 100%; anti-THP-DT = 96%; anti-epithelial membrane antigen-DT and collecting duct = 90% and 93%, respectively, and anti- cytokeratin 19-DT and collecting duct = 86% and 89% of the cases, respectively; (b) cystic areas: lotus tetrago- nolubus agglutinin, anti- CD15, anti-PTH, anti-epithelial membrane antigen, and anti-cytokeratin 19 = 7, 6, 18, 97, and 95% of the cases, respectively. Anti-vimentin was nonreactive. The results indicated that the cysts in cases of autosomal dominant polycystic kidney disease have an immunohistochemical profile of distal tubules and collecting ducts.
Keywords: Autosomal dominant polycystic kidney disease; Histogenesis; Immunohistochemistry; Lectins